Development of Packaging for Mango Nam Dok Mai from Sugarcane Leaf Fibers and Residue Asparagus - Theamdee, Pawinee; Sewakhuntos, Suphakit (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research aims to study the preparation of fruit packaging made from sugarcane leaf fibers and asparagus residue for packaging Nam Dok Mai mangoes. It examines different ratios of sugarcane leaf fibers and asparagus residue. The sugarcane leaf fibers were prepared using 10 % w/v sodium hydroxide at a temperature of 80 - 90 oC for 2 hours. The fibers were then bleached with 25 % v/v hydrogen peroxide for 1 hour. Meanwhile, the asparagus residue was dried in a hot air oven at 50 oC for 24 hours to obtain asparagus residue powder. The functional groups of the bleached sugarcane leaf fibers were analyzed using FTIR to confirm the presence of cellulose. Next, prepare the ratio for molding fruit packaging from sugarcane leaf fibers to asparagus powder, including 0:30 (S0A30), 10:20 (S10A20), 20:30 (S20A10), and 30:0 (S30A0) in grams. The fruit packaging was then molded based on the average dimensions of ripe Nam Dok Mai mangoes using a plaster mold. The samples were analyzed for their physical, chemical, and mechanical properties, including thickness, water absorption, water solubility, moisture absorption, compression test, puncture resistance, shear resistance, and biodegradability. The results indicated that the optimal ratio for packaging preparation was 20 grams of sugarcane leaf fiber to 10 grams of asparagus residue powder (S20A10). This ratio yielded the best overall physical, chemical, and mechanical properties. The resulting packaging had a smooth and uniform surface, low water absorption, water solubility, and moisture uptake. Additionally, it exhibited good compressive strength, puncture resistance, and shear resistance. Biodegradability testing through soil burial showed a decomposition rate 6.36 % over a period of 3 months. Therefore, the prototype fruit packaging made from asparagus residue and sugarcane leaf fibers can be used for packaging Nam Dok Mai mangoes and other related applications.